The impact of publicly funded immunization programs on human papillomavirus vaccination in boys and girls: An observational study - Gilla K. Shapiro; Ovidiu Tatar; Bärbel Knäuper; Gabrielle Griffin-Mathieu; Zeev Rosberger (Elsevier, 2022)
Summary: Background: Reaching and maintaining high global human papillomavirus (HPV) vaccine uptake has been challenging. The impact of publicly funded HPV immunization programs and the interplay of sociodemographic, psychosocial and policy factors in maximizing vaccination is poorly understood. This observational study examined the impact of introducing publicly funded school-based HPV vaccination programs for boys directly on uptake in boys and indirectly on uptake in girls, while concurrently examining other important sociodemographic and psychosocial factors. Methods: Data were collected from a national, longitudinal sample of Canadian parents of children aged 9-16 years during August-September 2016 (T1) and June-July 2017 (T2). Participants completed an online questionnaire measuring sociodemographic characteristics, vaccine knowledge and attitudes, health care provider recommendation, and HPV vaccine uptake. Analyses were conducted separately for parents of boys and girls using logistic regression analyses at T1 and T2. Jurisdictions with HPV vaccine funding for boys at both time-points were compared to those with funding at neither time-points and those that introduced funding between time-points. Findings: The sample included parents of boys (n = 716) and girls (n = 843). In multivariable analyses, jurisdictions with funding for boys at both time-points had higher odds of vaccination (adjusted odds ratio, T1 = 10.18, T2 = 11.42; 95% confidence interval, T1 = 3.08-33.58, T2 = 5.61-23.23) than jurisdictions without funding at both time-points; however, funded jurisdictions did not have higher odds of vaccination compared to jurisdictions that newly introduced funding for boys. Vaccination was associated with consistent determinants in boys and girls including child's age, health care provider recommendation, perceived vaccine harms, and perceived vaccine affordability. Interpretation: This gender-sensitive analysis highlights the interplay of sociodemographic, psychosocial, and policy factors that can improve HPV vaccination. Publicly funded school-based programs are an impactful strategy to increase vaccine uptake. Funding: This work was supported by the Canadian Cancer Society Research Institute (#704,036). GKS was supported by the Vanier Canada Graduate Scholarship and Queen Elizabeth II Diamond Jubilee Scholarship programs. The funders of this work had no role in the data collection, analysis, or interpretation, or any aspect pertinent to the study.